Time-to-positivity in bloodstream infection for Candida species as a prognostic marker for mortality. (5th April 2023) - Keighley, Caitlin; Pope, Alun L; Marriott, Debbie; Chen, Sharon C-A; Slavin, Monica A; ,
Abstract: Time-to-positivity (TTP) may assist in predicting the outcome of candidaemia. We analysed a candidaemia dataset collected prospectively in Australia over 1 year (2014–2015). TTP was defined as the period from blood culture sampling to the blood culture flagging positive. Of 415 candidaemia episodes, overall, 30-day mortality was 29% (120/415); mortality with Candida albicans was 35% (59/169), C. glabrata complex, 37% (43/115), C. tropicalis, 43% (10/23), Pichia kudriavzevii 25% (3/12), and C. parapsilosis complex 7% (5/71). Each day of increased TTP multiplied the odds ratio (OR) of survival at 30 days by a factor of 1.32 [95% confidence interval (CI) 1.06–1.69]. Shorter TTP was associated with increased mortality, with 1-day TTP associated with 30-day mortality 37% (41/112) (95%CI: 28%–46%) and 5-day TTP 11% (2/18) (95%CI: 2%–36%). Lay Summary: Time-to-positivity is a measure that is available to clinicians when patients are identified as having candida in their bloodstream. Our data support the association of a shorter time to positivity with higher mortality.